2019
DOI: 10.1136/jnnp-2018-319838
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical and genetic features of amyotrophic lateral sclerosis across Cuban, Uruguayan and Irish clinic-based populations

Abstract: ObjectivesThis study compares the clinical characteristics of patients with amyotrophic lateral sclerosis (ALS) within three clinic-based populations from Cuba, Uruguay and Ireland and determines the impact of known ALS-associated genetic variants on phenotypic manifestations within the Cuban population.MethodsDemographic and clinical information was collected on 115 Cuban, 220 Uruguayan and 1038 Irish patients with ALS attending national specialist clinics through 1996–2017. All Cuban patients and 676 Irish p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Recent studies have shown that the mean or median age of ALS onset is between 51 and 66 years [1 ▪ ,3,4 ▪ ,5,6,7 ▪▪ ,18 ▪ ,19,20,23,26,2831,32 ▪▪ ]. Patients in Europe have usually a later age at ALS onset compared with patients from China, Cuba, and Uruguay.…”
Section: Age At Onsetmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the mean or median age of ALS onset is between 51 and 66 years [1 ▪ ,3,4 ▪ ,5,6,7 ▪▪ ,18 ▪ ,19,20,23,26,2831,32 ▪▪ ]. Patients in Europe have usually a later age at ALS onset compared with patients from China, Cuba, and Uruguay.…”
Section: Age At Onsetmentioning
confidence: 99%
“…For example, Dorst et al [18 ▪ ] showed that Chinese ALS patients had a median age of ALS onset at 51 years, whereas the median age of ALS onset was around 10 years later among German ALS patients. Furthermore, the mean age at ALS onset was found to be 4–9 years smaller in Cuba and Uruguay compared with Ireland [26]. Population-based studies are more likely to include patients with the entire spectrum of disease characteristics, whereas clinic-based studies are more likely to include patients with specific characteristics (e.g., younger age at onset or slower disease progression) [33].…”
Section: Age At Onsetmentioning
confidence: 99%
“…The men to women ratio in the study sample was 1.4, and the ratio described in the literature is 1-2 [19][20][21]. The mean age of ALS onset was 53.61 years (while the average is 51-66 years) [18,[21][22][23][24], and 68% of the patients had spinal disorders (literature average 58-82%) [25][26][27]. Such a distribution in a relatively large group of patients allows for drawing conclusions and transposing them to the general population of ALS patients.…”
Section: Discussionmentioning
confidence: 60%
“…The men to women ratio in the study sample was 1.4, and the ratio described in the literature is 1-2 [19][20][21]. The mean age of ALS onset was 53.61 years (while the average is 51-66 years) [18,[21][22][23][24], and 68% of the patients had spinal disorders (literature average 58-82%) [25][26][27]. Such a distribution in a relatively large group of patients allows drawing conclusions and transposing them to the general population of ALS patients.…”
Section: Resultsmentioning
confidence: 99%